Efeito de diferentes métodos de conservação sobre os compostos bioativos e atividade antioxidante de mangaba (Hancornia speciosa Gomes) - Paula, Ladyslene Christhyns de (2015)
Brazil is a country of great diversity in species of native fruits, yet little explored, but with huge agro-industrial and nutritional potential, being mangaba one of these promising fruit. Research indicates that the intake of conventional, exotic and native fruits provide not only essential nutrients, but also bioactive compounds that promote beneficial effects on human health, reducing the risk of chronic diseases and even cancer, due to the interaction between these compounds and their antioxidant potential. This study aimed to evaluate the behavior of bioactive compounds and antioxidant activity in raw fruits mangaba (Hancornia speciosa Gomes), and the influence of conservation methods: freezing, freeze-drying and foam layer before these biocompounds. The samples were evaluated at Chemistry and Biochemistry Laboratory of Food of Faculty of Pharmacy of Federal University of Goiás, as regard of: ascorbic acid, phenolic compounds, carotenoids and total antioxidant activity by DPPH methods, ABTS and FRAP. Analyses were performed in triplicate for each sample, and the results were expressed as mean ± standard deviation. The results showed significant correlation between the content of total phenolic compounds and total antioxidant activity by FRAP method, showing that ascorbic acid content, contributed to the antioxidant activity of the samples. Thus, there is a possibility of using mangaba, both for consumption and fresh using, referred to as different methods of preservation, possibly enabling the use of the fruit as a functional food.